(untitled) (Journal of Architectural Design, 2024)
This article brings information about an improved comprehensive approach to improving the efficiency of energy management of residential buildings, a comprehensive approach to improving the energy efficiency of buildings, methods for assessing the effectiveness of energy-saving solutions